Application of Morphological Index in the Assesment of Type and Function of Fat Tail Sheep in Sapudi Island - A. M Abdurrahman; Setiasih Setiasih (University of Brawijaya, 2017)
Morphological index could be used to evaluate type and function of livestock. The aim of this study was applying morphological index to assess the type and function of Sapudi fat tail sheep. About 65 headewes comprising 32 ewes from Gayam village of Gayam district and 33 ewes from Talaga village of Nonggunung district were analysed. Morphology observed were body weight, body length, height at wither, heart girth, chest width, chest depth, hip width, rump height, rump length, tail length, and tail width. Index used were weight, height slope index, length index, width slope index, depth index, foreleg length index, balance, and cumulative index. Data of morphology obtained were analysed by descriptive and pearson correlation. The results show that the average of body measurements of Gayam fat tail sheep was higher than that of Talaga fat tail sheep. Talaga fat tail sheep had balance better than that of Gayam fat tail sheep. Sapudi fat tail sheep were high type and potential to be developed as meat animal.